A six year longitudinal study of the occupational consequences of drinking over "safe limits" of alcohol. Issue 5 (May 1992) - Jenkins, R; Harvey, S; Butler, T; Thomas, R L
Abstract : Although much research has focused on the psychological, social, and economic consequences of heavy problem drinking, there has been far less attention paid to the consequences of "moderate" drinking. This study used a unique opportunity to carry out a six year follow up of a cohort of male and female white collar workers in whom there was baseline information on alcohol consumption and access to details on sickness absence, labour turnover, and promotion. It has provided evidence that even moderate alcohol consumption in the working population is associated with social costs for the employer and the employee, including substantial sickness absence, and lack of promotion in men, although the increase in labour turnover was not statistically significant. The longitudinal examination of consumption in this study suggests that early intervention in a drinking career may reduce alcohol consumption and consequently avoid years of morbidity and sickness absence, as well as having a favourable influence on performance and labour turnover.